ANALISIS CASH HOLDING BERBASIS KEKUATAN KAS DAN MODAL KERJA BERSIH - Astuti, Anggita Windi (Universitas Muhammadiyah Yogyakarta, 2019)
This study aims to determine the effect of cash flow, cash conversion cycle, and net working capital on cash holding in the 2014-2018 food and beverage sub-sector companies partially or simultaneously. The population used in this study are all food and beverages sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample used using the purposive sampling method, so that a total of 55 research samples were obtained. The data analysis technique used is the multiple regression analysis method with a significant level of 5% (0.05). From the results of the study, it can be concluded that cash flow has no effect on cash holding. While the cash conversion cycle variable has a significant negative effect on cash holding. The variable net working capital has a significant positive effect on cash holding. The ability of independent variables to explain the relationship of the dependent variable is cash holding by 20.7% while the remaining 79.3% is influenced by other factors not examined in this study.Keywords: Cash flow, cash conversion cycle, net working capital and cash holding.